Molecular perturbations in cholangiocarcinoma: is it time for precision medicine? - Braconi, Chiara; Rössler, Stephanie; Kruk, Beata; Lammert, Frank; Krawczyk, Marcin; Brandt Andersen, Jesper (Liver international, 2019)
The complexity of cholangiocarcinoma (CCA) cellularity and the molecular perturbation mechanisms that underlie the diversity of growth patterns of this malignancy remain a clinical concern. Tumours of the biliary system display significant intrinsic chemoresistance, caused by significant stromal involvement and genome-wide tumour heterogeneity, hampering disease remission and palliation as well as promoting the metastatic behaviour. It is crucial to advance our present understanding of the risk and molecular pathogenesis of CCA. This will facilitate the delineation of patient subsets based on molecular perturbations and adjust for precision therapies.
Gesehen am 18.03.2020